Simultaneous bioethanol distillery wastewater treatment and xylanase production by the phyllosphere yeast Pseudozyma antarctica GB-4(0) - Watanabe, Takashi; Suzuki, Ken; Sato, Ikuo; Morita, Tomotake; Koike, Hideaki; Shinozaki, Yukiko; Ueda, Hirokazu; Koitabashi, Motoo; Kitamoto, Hiroko K (BioMed Central Ltd., 2015)
Abstract Bioethanol production using lignocellulosic biomass generates lignocellulosic bioethanol distillery wastewater (LBDW) that contains a large amount of xylose, making it a potential inexpensive source of xylose for biomaterials production. The main goal of this study was the production of useful enzymes from LBDW during treatment of this wastewater. In this study, we found that xylose strongly induced two yeast strains, Pseudozyma antarctica T-34 and GB-4(0), to produce novel xylanases, PaXynT and PaXynG, respectively. The nucleotide sequence of PaXynT [accession No. DF196774 (GAC73192.1)], obtained from the genome database of strain T-34 using its N-terminal amino acid sequence, was 91% identical to that of PaXynG (accession No. AB901085), and the deduced amino acid sequence is 98% identical. The specific activities of the purified PaXynT and PaXynG were about 52 U/mg. The optimal pH and temperature for both enzymes’ activities were 5.2 and 50°C, respectively. They hydrolyzed xylan to xylose and neither had β -xylosidase (EC 3.2.1.37) activity, indicating that they are endo- β -xylanases (EC 3.2.1.8). With these results, we expect that PaXyns can be employed in saccharizing lignocellulosic biomass materials for the production of useful products just like other endoxylanases. After 72 h of LBDW fed-batch cultivation using a jar-fermentor, strain GB-4(0) produced 17.3 U/ml (corresponding to about 0.3 g/l) of PaXynG and removed 63% of dissolved organic carbon and 87% of dissolved total phosphorus from LBDW. These results demonstrate the potential of P. antarctica for xylanase production during LBDW treatment.